Determination of peak oxygen uptake, the anaerobic threshold and efficiency in Paralympic sitting sports - With emphasis on the influence of test mode and protocol - Baumgart, J. K. (Norwegian University of Science and Technology, Faculty of Medicine and Health Sciences, Department of Neuromedicine and Movement Science, 2018)
Endurance exercise performance is mainly determined by peak oxygen uptake (VO2peak), percentage of VO2peak used at the anaerobic threshold and efficiency. Furthermore, a high VO2peak increases tolerance for higher training volumes and reduces recovery times between training sessions. However, there is lack of knowledge on how to assess endurance exercise performance in sport-specific modes in athletes with disabilities competing in different Paralympic sitting sports disciplines. For sitting Para cross-country skiers, Para biathletes and Para ice hockey players, the upper-body poling mode (UBP) may be the most sport-specific. Therefore, the main aim of the studies conducted in the course of this PhD was to determine VO2peak, the anaerobic threshold and efficiency in Paralympic sitting sports, with emphasis on the influence of test mode and protocol on these factors. Initially, a systematic literature review (Paper I) was conducted, including a metaanalysis to investigate differences in VO2peak between Paralympic sitting sports and a pooleddata analysis to investigate the effect of age, sex, body-mass, disability and test mode on VO2peak. Thereafter, three experimental studies (Paper II .. IV) were conducted using the UBP mode. In the three experimental studies, VO2peak and efficiency were compared between the UBP and the arm crank ergometry (ACE) mode (Paper II), the test-retest reliability of physiological parameters was investigated in the UBP mode (Paper III), and aerobic and anaerobic thresholds were investigated in the UBP mode (Paper IV). The main findings were that differences in VO2peak values between Paralympic sitting sports were fairly well reflected by the sport-specific demands and therefore, highest in sports with continuously high physical efforts such as Para cross-country sit skiing. In wheelchair athletes, being a man, not being tetraplegic or having an amputation compared to being paraplegic and testing in the wheelchair ergometry or wheelchair treadmill mode compared to the ACE mode was favourable for high VO2peak (Paper I). VO2peak did not differ between restricted UBP and restricted ACE, whereas VO2peak was lower in the paraplegic participants compared to the able-bodied cross-country skiers. Furthermore, exercise efficiency was lower in restricted UBP compared to restricted ACE (Paper II). In the UBP mode, the relative testretest reliability of VO2peak during a 1-min, a 3-min and an incremental upper-body poling test was high in able-bodied cross-country skiers. However, VO2peak was significantly higher during a 3-min closed-end and an open-end incremental test compared to a 1-min closed-end test (Paper III). When testing Para ice hockey players in the UBP mode, the physiological outcome parameters identified at the ventilatory threshold were significantly higher than the ones identified with fixed methods at the first lactate threshold, even though both are used to determine the aerobic threshold. In comparison, the outcome parameters at the respiratory compensation threshold and the second lactate threshold, which both determine the anaerobic threshold, and the ones identified at the ventilatory threshold were closely located. Furthermore, continuous linear and curvilinear (i.e. no-breakpoint) models fitted the gas exchange data of most Para ice hockey players during UBP better than breakpoint models (Paper IV). Overall, the findings of the studies conducted during this PhD show that participating in endurance sports with continuously high movement demands, being a man, not being tetraplegic or having an amputation, as well as testing in a wheelchair treadmill or wheelchair ergometer mode are favourable for high absolute and body-mass VO2peak values. Movement differences between UBP and ACE do not seem to have an impact on VO2peak when the upperbody is restricted, but the discontinuous power production in UBP leads to lower efficiency. Compared to able-bodied participants, spinal-cord injury related limitations negatively impact on VO2peak but not on efficiency in paraplegic participants. In UBP, both the 3-min and an incremental test are reliable VO2peak tests. Furthermore, the ventilatory threshold and first lactate threshold cannot be used interchangeably to identify the aerobic threshold. The close location of the ventilatory threshold, the respiratory compensation threshold and the second lactate threshold does not allow us to distinguish the aerobic and anaerobic threshold, indicating the presence of only one threshold in athletes with a disability exercising in UBP. In addition, it is questionable if clear breakpoints exist in the gas exchange data of athletes with a disability during UBP.